Effect of guanylin peptides on pancreas steatosis and function in experimental diet-induced obesity and after bariatric surgery - Otero, Aarón; Becerril, Sara; Martín, Marina; Cienfuegos, Javier A.; Valentí, Víctor; Moncada, Rafael; Catalán, Victoria; Gómez-Ambrosi, Javier; Burrell, María A.; Frühbeck, Gema; Rodríguez, Amaia (Frontiers in Endocrinology, 2023)
Obesity contributes to ectopic fat deposition in non-adipose organs, including the pancreas. Pancreas steatosis associates with inflammation and β-cell dysfunction, contributing to the onset of insulin resistance and type 2 diabetes. An improvement of pancreatic steatosis and indices of insulin resistance is observed following bariatric surgery, but the underlying mechanisms remain unknown. We sought to analyze whether guanylin (GUCA2A) and uroguanylin (GUCA2B), two gut hormones involved in the regulation of satiety, food preference and adiposity, are involved in the amelioration of pancreas fat accumulation after bariatric surgery. Pancreas steatosis, inflammation, islet number and area were measured in male Wistar rats with diet-induced obesity (n=125) subjected to surgical (sham operation and sleeve gastrectomy) or dietary (pair-fed to the amount of food eaten by gastrectomized animals) interventions. The tissue distribution of guanylate cyclase C (GUCY2C) and the expression of the guanylin system were evaluated in rat pancreata by real-time PCR, Western-blot and immunohistochemistry. The effect of guanylin and uroguanylin on factors involved in insulin secretion and lipogenesis was determined in vitro in RIN-m5F β-cells exposed to lipotoxic conditions. Sleeve gastrectomy reduced pancreas steatosis and inflammation and improved insulin sensitivity and synthesis. An upregulation of GUCA2A and GUCY2C, but not GUCA2B, was observed in pancreata from rats with diet-induced obesity one month after sleeve gastrectomy. Interestingly, both guanylin and uroguanylin diminished the lipotoxicity in palmitate-treated RIN-m5F β-cells, evidenced by lower steatosis and downregulated lipogenic factors Srebf1, Mogat2 and Dgat1. Both guanylin peptides reduced insulin synthesis (Ins1 and Ins2) and release from RIN-m5F β-cells, but only guanylin upregulated Wnt4, a factor that controls β-cell proliferation and function. Together, guanylin, and to a lesser extent uroguanylin, constitute protective factors against pancreas steatosis. Increased GUCA2A expression levels in the pancreata after bariatric surgery might contribute to improve pancreas steatosis, inflammation and β-cell function.